THE CONCEPT OF CULTURAL NATIONALISM AND ITS IMPLEMENTATION IN IRELAND IN THE 19th – EARLY 20th CENTURIES - Miroshnikov A. V.; Shishkina I. B. (Вестник Брянского государственного университета)
In the article, the authors attempt to analyze one of the most important components of the Irish national movement of the 19th – early 20th centuries, cultural nationalism. Irish nationalism throughout its history has tended to variously highlight issues of political liberation or self-government, agrarian and religious issues. Priorities largely depended both on the prevailing ideas of the leaders of the movement in a particular period, and on the corresponding political and social atmosphere. An important role was also played by the commitment of the leaders of nationalist organizations to the methodology for implementing their programs, be it “physical” or “moral strength”. However, the total dictatorship of Britain in imposing English culture, language, traditions, education with severe pressure on Irish culture, demanded from nationalists the formation of the identity of the Irish nation, the renovation of the rich national heritage. With the change in the social state of society at the turn of the 19th and 20th centuries, cultural nationalism gained a huge audience, while updating new directions in culture. The revolution of 1916-1923, while solving the problem of winning independence, also included the problem of national self-identification.